Platelet Glycoprotein Receptor IIIa Polymorphism PlA1/PlA2 and Coronary Risk: a Meta-Analysis - Castelnuovo, Augusto Di; Gaetano, Giovanni de; Donati, Maria Benedetta; Iacoviello, Licia (Thrombosis and Haemostasis, 2001)
Membrane glycoprotein IIb/IIIa plays a major role in platelet function. The gene encoding the glycoprotein IIIa shows a common polymorphism PlA1/PlA2 that was variably associated with vascular disease. To clarify the role of PlA1/PlA2 polymorphism in coronary risk, a meta-analysis of published data was conducted. Studies were identified both by MEDLINE searches, and hand searching of journals and abstract books.A total of 34 studies for coronary artery disease (CAD), and 6 for restenosis after revascularization were identified, for a total of 9,095 cases and 12,508 controls. In CAD, the overall odds ratio for carriers of the PlA2 allele was 1.10 (95% CI: 1.03 to 1.18), and it was 1.21 (95% CI: 1.05 to 1.38) in subjects younger than 60. Overall odds ratio was 1.31 (95% CI: 1.10 to 1.56) after revascularization procedures.The association of PlA2 status with overall cardiovascular disease in the general population is significant but weak; higher risk has been identified in less heterogeneous subgroups as in the younger cohorts and in the restenosis subset with stents.
Keywords: Coronary disease; genes; platelet glycoprotein; PlA1/PlA2 polymorphism; meta-analysis